The Extent of Compatibility Between National Mechanisms and International Mechanisms to Combat Corruption - Jabr, Naseer Jassim (Indonesian Journal Publisher, 2025)
This study aims to analyze the extent to which national mechanisms for combating corruption align with international mechanisms, particularly in the context of Iraq. The research focuses on the harmonization between national laws and oversight institutions with international conventions ratified by Iraq, such as the United Nations Convention Against Corruption (UNCAC) 2003. The research methodology employs an analytical approach by examining international treaty texts and national laws, as well as a comparative approach to assess the alignment between international agreements and domestic legislation. The findings indicate that although Iraq has made efforts toward harmonization through the ratification of international conventions and the enactment of anti-corruption laws, challenges remain in their implementation. These challenges include weak governmental institutions, political party interference, and a lack of public trust. This study recommends strengthening oversight institutions, enhancing transparency, and increasing public participation in the fight against corruption.